2004
DOI: 10.1038/sj.ejcn.1602063
|View full text |Cite
|
Sign up to set email alerts
|

Participatory nutrition education and adoption of new feeding practices are associated with improved adequacy of complementary diets among rural Malawian children: a pilot study

Abstract: Objective: To introduce practices for improving complementary feeding and evaluate their adoption and association with improved dietary intakes. Design: A quasiexperimental pilot study comparing dietary intakes from complementary foods among three intervention communities and one control community before and after the intervention, and adoption of new complementary feeding practices among intervention communities following the intervention. Setting: Rural subsistence communities in southern Malawi, Central Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 29 publications
4
90
3
Order By: Relevance
“…Nutrition education has been shown to improve nutritional behaviour and practices [37,38]. This is against the background that some of the taboos have persisted due to lack of an understanding of the nutritional benefits of prohibited foods.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition education has been shown to improve nutritional behaviour and practices [37,38]. This is against the background that some of the taboos have persisted due to lack of an understanding of the nutritional benefits of prohibited foods.…”
Section: Discussionmentioning
confidence: 99%
“…Gibson (2001, 2005) have carried out several nutrition interventions to improve complementary feeding practices in Malawi. The approach used involved pilot testing different recipes that would increase the nutritional value of complementary foods and promoting a series of 'messages' for mothers about ways to improve complementary feeding (Hotz & Gibson, 2005). While integrating local cooking practices into their messages, the nutrition educational approach appears to be primarily an information transfer model focused on the mother (Lee & Garvin, 2003).…”
Section: Child Nutrition and Health Education Modelsmentioning
confidence: 99%
“…In addition, even when food resources are available in the home, caregivers might not make the best use of them due to lack of knowledge of the best foods for young children, cultural beliefs and practices, and inappropriate advice (14)(15)(16) . Studies on young children's feeding practices in other countries have demonstrated evidence that educational interventions have positive effects on knowledge of caregivers, complementary feeding practices and growth among children (17)(18)(19)(20)(21) .…”
mentioning
confidence: 99%